Atomic layer deposition and characterization of Bi1Se1 thin films - He, Shiyang; Bahrami, Amin; Zhang, Xiang; Cichocka, Magdalena Ola; Yang, Jun; Charvot, Jaroslav; Bureš, Filip; Heckel, Alla; Schulz, Stephan; Nielsch, Kornelius (Elsevier Science, 2023)
Van der Waals (vdWs) heterostructured materials have attracted considerable interest due to their intriguing physical properties. Here, we report on the deposition of BiSe by atomic layer deposition (ALD) using Bi(NMe2)3 and Se(SnMe3)2 as volatile and reactive Bi and Se precursors, respectively. The growth rate varies from 1.5 to 2.0 angstrom/cycle in the deposition temperature range of 90-120 degrees C. Higher deposition temperatures lead to increased grain sizes and enhanced crystallinity of resulting films. Further microstructure characterization reveals the formation of crystalline domains with varying orientations and nanotwinned boundaries. The presence of Bi-Bi zigzag bilayers and the formation of the BiSe phase were confirmed by the existence of the Bi-Bi binding energy peak in the XPS spectra and Raman spectra. Furthermore, the electrical conductivity of BiSe ranged from 1420 to 1520 S/cm due to the ultrahigh carrier concentration (2-3.5 x 1021 cm-3), which is the highest among undoped bismuth selenide-based materials.
Depozice atomárních vrstev a charakterizace tenkých filmů Bi1Se1
Keywords: Atomic layer deposition; Van der Waals heterostructured materials; BiSe; Carrier concentration; Depozice atomárních vrstev; Van der Waalsovy heterostrukturované materiály; BiSe, Carrierova koncentrace